GB Smart Meter Roll-out Programme: Right time for starting the roll out - Shetty, Harshitha (2010)
Government of UK has issued a mandate to all utility suppliers in the country to ensure that smart meter is fitted in the premises of all their domestic customer by 2020 or earlier(DECC,2010). The main reason for governing bodies impose regulations is to reduce harmful emissions and also secure energy resources for future. This initiative of installing smart meter in every household is also linked to strengthening UK governments’ commitment to achieve its set target in reducing energy usage while empowering consumer with clear information of their usage and thus make a conscious effort to use, only required amount of energy.(DECC, 2010)